Effect of a ZrO2 Seed Layer on an Hf0.5Zr0.5O2 Ferroelectric Device Fabricated via Plasma Enhanced Atomic Layer Deposition - Song, Ji-Na; Oh, Min-Jung; Yoon, Chang-Bun (Materials, 2023)
In this study, a ferroelectric layer was formed on a ferroelectric device via plasma enhanced atomic layer deposition. The device used 50 nm thick TiN as upper and lower electrodes, and an Hf0.5Zr0.5O2 (HZO) ferroelectric material was applied to fabricate a metal–ferroelectric–metal-type capacitor. HZO ferroelectric devices were fabricated in accordance with three principles to improve their ferroelectric properties. First, the HZO nanolaminate thickness of the ferroelectric layers was varied. Second, heat treatment was performed at 450, 550, and 650 °C to investigate the changes in the ferroelectric characteristics as a function of the heat-treatment temperature. Finally, ferroelectric thin films were formed with or without seed layers. Electrical characteristics such as the I–E characteristics, P–E hysteresis, and fatigue endurance were analyzed using a semiconductor parameter analyzer. The crystallinity, component ratio, and thickness of the nanolaminates of the ferroelectric thin film were analyzed via X-ray diffraction, X-ray photoelectron spectroscopy, and transmission electron microscopy. The residual polarization of the (20,20)*3 device heat treated at 550 °C was 23.94 μC/cm2, whereas that of the D(20,20)*3 device was 28.18 μC/cm2, which improved the characteristics. In addition, in the fatigue endurance test, the wake-up effect was observed in specimens with bottom and dual seed layers, which exhibited excellent durability after 108 cycles.